Association between malocclusion, caries and oral hygiene in children 6 to 12 years old resident in suburban Nigeria - Kikelomo Adebanke Kolawole; Morenike Oluwatoyin Folayan (BMC, 2019)
Abstract Background There are conflicting opinions about the contribution of malocclusions to the development of dental caries and periodontal disease. This study's aim was to determine the association between specific malocclusion traits, caries, oral hygiene and periodontal health for children 6 to 12 years old. Methods The study was a household survey. The presence of malocclusion traits was assessed in 495 participants. The caries status and severity were assessed with the decayed, missing, and filled teeth (dmft/DMFT) index and the pulpal involvement, ulceration, fistula and abscess (pufa/PUFA) index. The Simplified Oral Hygiene Index (OHI-S) and Gingival Index (GI) were used to assess periodontal health. The association between malocclusion traits, the presence of caries, poor oral hygiene, and poor gingival health were determined with chi square and logistic regression analyses. Statistical significance was inferred at p < 0.05. Results Seventy-four (14.9%) study participants had caries, with mean (SD) dmft/DMFT scores of 0.27 (0.82) and 0.07 (0.39), respectively, and mean (SD) pufa/PUFA index scores of 0.09 (0.43) and 0.02 (0.20), respectively. The mean (SD) OHI-S score was 1.56 (0.74) and mean (SD) GI score was 0.90 (0.43). Dental Aesthetic Index scores ranged from 13 to 48 with a mean (SD) score of 20.7 (4.57). Significantly greater proportions of participants with crowding (p = 0.026) and buccal crossbite (p = 0.009) had caries. Significantly more children with increased overjet (p = 0.003) and anterior open bite (p = 0.008) had moderate to severe gingivitis. Poor oral hygiene (OR: 1.83; CI: 1.05-3.18 p = 0.033), crowding (OR: 1.97; CI: 1.01-3.49; p = 0.021) and buccal crossbite (OR: 6.57; CI: 1.51-28.51 p = 0.012) significantly increased the odds of having caries. Poor oral hygiene (p < 0.001), increased overjet (p = 0.003), and anterior open bite (p = 0.014) were the only significant traits associated with gingivitis. Conclusions Crowding and buccal cross bite were associated with caries, whereas increased overjet and anterior open bite were associated with gingivitis. These findings justify the recommendation of orthodontic treatment to improve oral health.